Ecological study on mortality from influenza and pneumonia before and after influenza vaccination in the Northeast and South of Brazil - Janessa de Fátima Morgado de Oliveira; Antonio Fernando Boing; Eliseu Alves Waldman; José Leopoldo Ferreira Antunes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The study compared mortality from influenza and pneumonia in elderly people (65 years or older) before and since implementation of influenza vaccination in the South and Northeast regions of Brazil. Official population and mortality data were retrieved from government agencies to estimate weekly mortality rates. The Serfling model was used to identify influenza outbreaks and estimate the mortality attributable to them. In the South, the vaccination period showed a major reduction in mortality from influenza and pneumonia and in the number and duration of influenza outbreaks. These results were interpreted as consistent with the hypothesis of the vaccination program's effectiveness. In the Northeast, there was an increase in mortality from influenza and pneumonia during vaccination, which was associated with a quality improvement in recording causes of death in the elderly. An increase was also seen in mortality attributable to influenza outbreaks, suggesting a mismatch between the period in which vaccination is conducted and the relevant climatic characteristics for influenza transmission.